Manifestations II Indian art in the 20th century : 100 artists from the DAG collection - Karode, Roobina (Delhi Art Gallery, 2004)
Exhibited at the Jehangir Art Gallery, Mumbai, July 25th to 31st, 2004 and Delhi Art Gallery, New Delhi, August 9th to 21st, 2004; includes biographical sketches of contemporary Indian artists.